Prevalence of polycystic ovary syndrome by the international evidence-based guidelines: A nationwide cross-sectional survey - Illiyas, Samirah Binte; Morshed, Md. Shahed; Hasan, Mashfiqul; Tofail, Tania; Banu, Hurjahan; Sultana, Nusrat; Siddika, Munira Afroz; Islam, Md. Rafayel; Mahrukh, Hafsa; Ferdousi, Tahmina; et al. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Data regarding the nationwide prevalence of polycystic ovary syndrome (PCOS) in Bangladeshi women is scarce. Additionally, a prevalence study using the stepwise decision-making approach, incorporating antimüllerian hormone (AMH), was also not reported. Objectives: To determine the prevalence and characteristics of PCOS and its isolated diagnostic features among Bangladeshi women aged 10-45 years, using the 2023 International Evidence-based Guidelines, including AMH. Methods: From April to September 2024, 1201 females were sampled across eight divisions of Bangladesh by history, physical examinations, and blood collection. Total testosterone (TT) and AMH levels were assessed, with specific cut-offs established from a healthy control group. Thyroid dysfunction and hyperprolactinemia were excluded. Results: Of 1201 participants, 403 were excluded. Among 798 eligible women, 38 (4.8%) had both irregular cycles and significant hirsutism, 75 (9.4%) had only significant hirsutism, 141 (17.7%) had only irregular cycles, and 544 (68.2%) had neither. After TT and AMH evaluation and excluding two hyperprolactinemia cases, a 6.9% (55/798) prevalence was found among 57 women with probable PCOS. Familial predisposition, unhealthy sleep behaviour, and higher androgenic and metabolic features were observed in women with PCOS versus controls. Metabolic syndrome frequency was higher among adult PCOS (33.3% vs. 4.0%) than adolescent PCOS. Conclusions: The prevalence of PCOS among Bangladeshi women was 6.9%, with distinctive features compared to controls. Women with isolated diagnostic criteria require further evaluation and long-term follow-up. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S37]